Išorinė atviroji sandūra bendrinėje lietuvių kalboje (audicinis tyrinėjimas) - Strimaitienė, Marija (Kalbotyra, 1983)
An auditory experiment was carried out at the Experimental Phonetics Laboratory of Vilnius V. Kapsukas University to ascertain whether auditors differentiate clusters with external open juncture from clusters without it. The experiment showed: (1) Standard Lithuanian, no doubt, possesses external open juncture – interword consonant clusters were distinguished from innerword clusters; (2) the presence of the juncture was perceived much better and with greater accuracy than the absence of the juncture. This points to a certain optionality of external open juncture in Lithuanian.